Association of VDR gene polymorphisms with prediabetes and Type 2 diabetes mellitus in a sample of the Iranian population - Dorsa Salabat; Nekoo Panahi; Noushin Fahimfar; Masoud Saeedi; Hanieh Radkhah; Abbasali Keshtkar; Hamid Reza Aghaei Meybodi; Afshin Ostovar; Bagher Larijani; Mahsa M. Amoli (PLoS ONE, 2026)
Background Type 2 diabetes mellitus (T2DM) is a prevalent chronic disorder responsible for most diabetes cases. The role of vitamin D receptor ( VDR ) gene variants in T2DM susceptibility has been investigated previously; however, the results are contradictory, particularly among diverse ethnic groups. This study aimed to investigate the association between VDR gene polymorphisms and T2DM in a sample of the Iranian population. Methods Data from 976 participants of the phase 3 Iranian Multicenter Osteoporosis Study (IMOS) were analyzed. Five VDR polymorphisms (ApaI, TaqI, EcoRV, FokI, and BsmI) were genotyped and assessed among diabetic (DM), prediabetic (preDM), and healthy participants. We employed logistic regression models to evaluate the association of VDR polymorphisms with preDM and DM, accounting for potential confounding factors, including age, gender, body mass index (BMI), and vitamin D levels. Results The multivariable logistic regression analysis indicated a significant relationship between the ApaI polymorphism (rs7975232) and the risk of developing preDM or DM. Specifically, individuals with the CC genotype exhibited a 66% increased likelihood of progressing to preDM or DM compared to those with the AA genotype [OR: 1.66 (1.07, 2.56)]. In examining the A dominant state, individuals carrying at least one A allele ( AA or AC genotypes) were found to be 35% less likely to develop preDM or DM when compared to those with the CC genotype [OR: 0.65 (0.43, 0.97)]. No significant associations were identified for the other polymorphisms (TaqI, EcoRV, FokI, and BsmI). Conclusion These findings indicate that the C allele of the ApaI polymorphism may be associated with an increased susceptibility to T2DM in this population, underscoring the VDR gene’s role in T2DM risk and pointing to potential personalized prevention and management strategies.